PARTISIPASI MASYARAKAT DAN STAKEHOLDER DALAM PENYELENGGARAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DAMPAKNYA TERHADAP KOMUNITAS PERDESAAN - Rosyida, Isma; Tonny Nasdian, Fredian (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
Empowerment is road to participation and participation determine social and economical community development program’s impacts. Generally, this research aims to identifiy the correlation between participation level of society and stakeholders in holding Corporate Social Responsibility program of Geothermal Corporation through Micro Finance Board and its impact to the society’s social and economical condition. This research was concerned to see the implementation of Community Based Micro Finance Program in Kabandungan District by holding LKMS Kartini. The subjects of this research were the society of Cihamerang Village, including its local government and local community, also corporate staffs. Methodes which are implied in this reseach consist of quantitative and qualitative study. Sample taken as many as fourty-five respondents who represent Cihamerang Village community, with the informant as many as nine persons. Results of this research shows that every stakeholders have different type and degree of participation. The higher micro finance board member’s participation level in every steps of program implementation, the higher social and economical impacts will be got.